Fiscal Sustainability with Non-Renewable Resources - Chalk, Nigel (IMF Working Papers; Working Paper, 1998)
This paper assesses sustainable fiscal behavior in an economy where wealth is derived predominantly from a non-renewable resource. It explores the issue in a simple dynamic framework that highlights the structural weaknesses in the underlying budgetary position, takes into account the rate of depletion of a country's natural resource base, and examines the impact of changes in a country's terms of trade. An alternative indicator of fiscal sustainability is derived, and the principal factors determining sustainability are identified. The results of the analysis are applied to Venezuela and Kuwait.